Pendampingan Guru-Guru SMA Darussalam dalam mendesain dan menerapkan Pembelajaran berbasis Digital - Ihdina Gustina; Putri Wahyuni; Dedy Lazuardi; Muammar Rinaldi; Sri Rezeki; Tina Muhardika Handayani (Lembaga Penelitian dan Pengabdian Masyarakat STIE Eka Prasetya, 2023)
The partners in the Community Partnership Program (PKM) activity plan are the teachers of Darusalam Medan Private High School in Medan Petisah District. Through the results of observations and interviews conducted by the proposing team, several priority problems were found by partners, namely: (1). The lack of knowledge of teachers about innovative learning methods so that learning takes place in a monotonous and boring way for students, (2). Teachers lack the knowledge and skills to develop teaching materials so they only use books from the library which are inadequate in number and quality, (3). Lack of opportunity to take part in free training to be able to develop and update teaching methods in accordance with educational developments in the industrial revolution era 4.0, (4) Schools do not yet have an online learning information system (e-learning), (5) Smartphones and laptops owned by students are only used for social media (Facebook, WhatsApp, Instagram), watching YouTube and playing online games during recess using internet facilities both at school and privately owned even though they should be used for learning. The solutions offered to solve partner problems are: 1). Carry out training on fun learning strategies and innovative learning methods for students in the form of blended learning, 2). Carry out training and assistance in the preparation of teaching materials for teachers, 3). Carry out training and mentoring the use of online learning information systems for teachers, 4). Making an online learning information system) that can be accessed via laptops and Android mobile phones, 5). Conduct user training for students. The approach method in implementing PKM uses education, training, practice, and mentoring methods